REMOVAL OF OXYTETRACYCLINE BY POLYMERS. AN OVERVIEW - Bernabe L Rivas; Pablo Oñate; Daniel A. Palacio (Journal of the Chilean Chemical Society, 2020)
Oxytetracycline (OTC) is an antibiotic belonging to the tetracycline family, widely used in veterinary medicine due to its pharmacological characteristics and adequate cost/effectiveness ratio.One of the problems presented by the therapeutic use of antibiotics such as OTC is that they do not metabolize and are expelled through animal excretions reaching the effluent of wastewater, rivers, and lagoons, causing accumulation and generating resistance to certain pathogens, mainly zoonotic bacteria.The above has presented the need and the challenge of removing this type of contaminants present in aquatic systems, using more efficient economic and eco-friendly methods than the conventional ones already known. A promising alternative is removal by using polymeric materials.Therefore, the aim of this revision is give a general revision of the application of functional polymer materials to remove these emerging organic contaminants OTC.